2017
DOI: 10.1080/24701394.2017.1350855
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and phylogenetic relationships of seven Amorphophallus species in southwestern China revealed by chloroplast DNA sequences

Abstract: Plants species in the genus Amorphophallus are of great economic importance, as they are the only plants known to produce glucomannan. Although southwestern China has been recognized as one of the origin centres of Amorphophallus, only a few studies assessing its genetic diversity have been reported. To aid in the utilization and conservation of Amorphophallus species, we evaluated the genetic diversity and phylogenetic relationships among seven edible Amorphophallus species using three chloroplast DNA regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…To date, the DNA sequence data for the Araceae family have mostly been obtained from chloroplasts and mitochondria ( Renner et al, 2004 ; Rothwell et al, 2004 ; Cusimano et al, 2011 ; Henriquez et al, 2014 ; Choi et al, 2017 ; Gao et al, 2018 ; Tian et al, 2018 ). With the exception of the whole-genome sequences of five species of the remotely related duckweeds ( Acosta et al, 2021 ), little information is available about the nuclear genes of Araceae species, including their rDNA.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the DNA sequence data for the Araceae family have mostly been obtained from chloroplasts and mitochondria ( Renner et al, 2004 ; Rothwell et al, 2004 ; Cusimano et al, 2011 ; Henriquez et al, 2014 ; Choi et al, 2017 ; Gao et al, 2018 ; Tian et al, 2018 ). With the exception of the whole-genome sequences of five species of the remotely related duckweeds ( Acosta et al, 2021 ), little information is available about the nuclear genes of Araceae species, including their rDNA.…”
Section: Introductionmentioning
confidence: 99%
“…In most angiosperms, the cpDNA is inherited through the maternal lineage, has a low mutation rate, and is rarely subject to recombination [15][16][17]. Estimates of genetic diversity based on cpDNA sequences can be used to provide inferences on the evolutionary history of plant species, including possible recolonization routes, diversification events, and gene flow [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to several other studies, such as Suriyagoda et al (2011); Rabara et al (2014) and Sinha et al (2015), this germplasm showed lower diversity. According to Gao et al (2017), low-level genetic diversity is affected by several factors, such as a founder effect, genetic isolation, population decline, natural selection or inbreeding. In this case, inbreeding was the most probable cause for the low level of diversity (Mursyidin et al, 2017).…”
Section: Importance Of Genetic Diversity and Its Related Factorsmentioning
confidence: 99%
“…Li (2003) predicted that the distribution of cultivated rice to Indonesia occurred around 1599 before the current era. During this process, inbreeding would have been unavoidable and may have reduced genetic diversity (Gao et al, 2017). Furthermore, reduced genetic diversity may correlate with decreasing disease resistance and resilience to environmental disturbance and extreme conditions (Lloyd et al, 2016).…”
Section: Importance Of Genetic Diversity and Its Related Factorsmentioning
confidence: 99%